FAKTOR-FAKTOR PEMENUHAN HAK WARGA NEGARA DALAM MEMBENTUK KEPUASAN PENGGUNA KRL JABODETABEK - Neisha Kusuma, Kayla; Rahmat; Bestari, Prayoga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Jabodetabek Commuter Line services represent the fulfillment of citizens’ rights to safe, comfortable, accessible, reliable, and equitable public services. This study aims to identify the rights-fulfillment factors associated with user satisfaction and to interpret them through service quality and civic knowledge perspectives. A quantitative survey was conducted among 400 active commuter rail users aged 17–45 years selected through purposive sampling. Data were collected using a questionnaire comprising 15 rights-fulfillment items and 15 user-satisfaction items and were analyzed using descriptive statistics and simple linear regression. The findings show that rights fulfillment collectively has a strong positive and significant relationship with user satisfaction. Security and physical protection emerged as prominent positive aspects, particularly the presence of security officers and the orderly operation of women-only carriages. Comfort, accessibility, reliability, affordability, and fairness also formed the service experience underlying satisfaction. In contrast, access to complaint channels and complaint submission procedures remained the weakest participatory aspects and therefore require priority improvement. The item-level factors are interpreted descriptively because the regression model tests the aggregate rights-fulfillment score rather than the independent effect of each factor. Civic knowledge is used as an interpretive lens to explain users’ ability to recognize, evaluate, and exercise their rights in public services.